2022
DOI: 10.1177/23821205221096361
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating “Webside Manner” at the UME-GME Transition Point During the COVID-19 Pandemic: A Novel Virtual Telemedicine Curriculum

Abstract: BACKGROUND Telemedicine use in the US has continued to grow over the past few years with the development of new technology and in response to the COVID-19 pandemic. This has led to a growing need for formal training in telemedicine for clinicians in order to improve communication skills and provide better patient outcomes. METHODS A self-directed, five-unit online curriculum focused on telemedicine essentials was developed through discussions among Pediatric clinical educators and adapted from literature in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…[17,18] A solution for this could include modules or courses to teach providers ways to better build rapport with patients when communicating electronically, which have been shown to increase communication scores. [19,20] Telemedicine proved particularly advantageous to our cohort when examining transportation -which almost 80% of respondents noted issues causing them to miss an appointment within the year prior to the pandemic. This finding is notable, especially in the context of our survey's location because Detroit is a city with limited public transportation, and it has been shown that urban Detroit men and women have to travel longer distances for daily activities compared to nearby suburban residents.…”
Section: Discussionmentioning
confidence: 99%
“…[17,18] A solution for this could include modules or courses to teach providers ways to better build rapport with patients when communicating electronically, which have been shown to increase communication scores. [19,20] Telemedicine proved particularly advantageous to our cohort when examining transportation -which almost 80% of respondents noted issues causing them to miss an appointment within the year prior to the pandemic. This finding is notable, especially in the context of our survey's location because Detroit is a city with limited public transportation, and it has been shown that urban Detroit men and women have to travel longer distances for daily activities compared to nearby suburban residents.…”
Section: Discussionmentioning
confidence: 99%
“…Acknowledge the limitations of the video visit and include that platforms allow only one person to speak at a time. Minimize interruptions and rely more on non-verbal responses such as nodding your head, raising your eyebrows to express concern, or leaning forwards rather than saying “hmm” or “yes” or “I know” while the patient is speaking, with an emphasis on webside manner [ 38 , 39 ].…”
Section: Best Practice Recommendationsmentioning
confidence: 99%